2011
DOI: 10.1002/eji.201141721
|View full text |Cite
|
Sign up to set email alerts
|

SH2‐domain mutations in STAT3 in hyper‐IgE syndrome patients result in impairment of IL‐10 function

Abstract: Autosomal-dominant hyper-IgE syndrome (AD-HIES) is a primary immunodeficiency caused by STAT3 mutations. This inherited condition is characterized by eczema, staphylococcal cold abscesses and recurrent pulmonary infections. Given that STAT3 is involved in IL-10 signaling, we examined the immunoregulatory role of IL-10 in inflammation by studying the effects of IL-10 on monocytes, neutrophils and monocyte-derived DCs from HIES subjects. Analysis of gene expression in PBMCs and neutrophils isolated from HIES pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…In addition, E2-2 demonstrates instructive function because its overexpression in CD34 ϩ thymic progenitors promotes pDC generation in the presence of Flt3L and IL-7 [232]. Individuals with STAT3 mutations that abrogate transcriptional activity (e.g., mutations in the DNA binding, SH2, or transactivation domains) have an impaired ability to produce tolerogenic DCs in response to IL-10, consistent with the role for STAT3 in IL-10 signal transduction [233][234][235]. In contrast, congenital Id2 mutations have not been associated with DC deficiency to date, although overexpression of Id2 or the related factor Id3 in CD34 ϩ progenitors inhibits pDC development in agreement with the negative role for Id2 in murine pDCs [231,236].…”
Section: Transcriptional Control Of Human Dcsmentioning
confidence: 70%
“…In addition, E2-2 demonstrates instructive function because its overexpression in CD34 ϩ thymic progenitors promotes pDC generation in the presence of Flt3L and IL-7 [232]. Individuals with STAT3 mutations that abrogate transcriptional activity (e.g., mutations in the DNA binding, SH2, or transactivation domains) have an impaired ability to produce tolerogenic DCs in response to IL-10, consistent with the role for STAT3 in IL-10 signal transduction [233][234][235]. In contrast, congenital Id2 mutations have not been associated with DC deficiency to date, although overexpression of Id2 or the related factor Id3 in CD34 ϩ progenitors inhibits pDC development in agreement with the negative role for Id2 in murine pDCs [231,236].…”
Section: Transcriptional Control Of Human Dcsmentioning
confidence: 70%
“…Despite a normal frequency of total CD4+ cells, we documented an increase in na€ ıve CD4+ T cells (71%) compared with normal donors (median 42%, range 35%-53%), as previously described in STAT3mut individuals (4); moreover, stimulation with IL-12 resulted in a reduction of IL-21 expression in na€ ıve CD4+ T cells (3.5%), compared with that observed in normal donors (median 32%, range (25%-39%)) (4). The addition of IL-10 to LPS-treated DC, contrary to what occurs in normal controls, did not affect their maturation, as indicated by the expression of maturation antigens CD1, CD80, and CD86 (5).…”
mentioning
confidence: 70%
“…To confirm the pathologic relevance of this newly identified mutation, immunologic tests were performed, as previously described (3)(4)(5). Accordingly with diagnostic guidelines proposed for hyper-IgE syndrome (3), the induction of Th17 cells after stimulation with the superantigen SEB was strongly impaired in the patient (0.05%) compared with age-matched healthy controls (0.52-0.76%).…”
mentioning
confidence: 99%
“…Moreover, Hong et al demonstrated that the BTK SH2 domain binds to phospholipids and the XLA-causing mutations alter lipid binding selectivity [174]. In another example, multiple point mutations within the transcription factor STAT3 SH2 domain have been identified and linked to large granular lymphocytic leukemia and the hyper-IgE syndrome [175,176]. In conjunction with the identification and study of SH2 domain-related diseases, small molecule inhibitors of SH2 domains, SH2 domain-containing proteins or SH2 binding partners, are being developed with some success as therapeutic reagents, although the development of phosphomimetics faces hurdles due to the strong charge of the phosphate group [177,178].…”
Section: Introductionmentioning
confidence: 99%